Optimal Allocation and Sizing of Multi DG Units Including Different Load Model Using Evolutionary Programming. Issue 1 (May 2021) - Mohammed, M. F.; Rahim, S R A; Azmi, A.; Wan Zanudin, W. Z.; Hussain, M H; Hashim, N; Aliman, O.
Abstract: This paper presents the optimal allocation and sizing of multi distributed generation (DG) units including different load models using evolutionary programming (EP) in solving power system optimization problem. This paper also studies on the effect of multi DG placement in different load model. To optimize the power distribution system, multi DG units were used to reduce losses power distribution system. By using EP, the optimal allocation and sizing of multi-DG was determined in order to obtain maximum benefits from its installation. The propose technique was tested into IEEE 69-bus distribution system. The result shows the placement of DG can reduce power loss 89% to 98%. The placement of multi-DG unit has better performance compare to single DG.